Modeling of bremsstrahlung emission from the confined runaway electrons and applications to the hard x-ray monitor of ITER. (5th October 2018) - Pandya, Santosh P; Core, Laura; Barnsley, Robin; Rosato, Joël; Reichle, Roger; Lehnen, Michael; Bertalot, Luciano; Walsh, Michael
Abstract: The importance of runaway electron (RE) detection, analysis of its parameters and suppression or mitigation is well recognized for large size tokamaks such as ITER. One of the well-established detection techniques is hard x-ray spectrometry that detects bremsstrahlung emission typically in the MeV range from the REs. It provides space, time and energy resolved measurements, which can also be utilized for the reconstruction of the RE energy distribution function. In this paper, forward modeling has been carried out for the detection of the confined REs and a numerical tool is developed. It calculates analytically anisotropic bremsstrahlung emissivity at each spatial position in the plasma in terms of several plasma, RE and geometrical parameters. The simulation provides line integrated energy resolved spectra of bremsstrahlung photons. The expected bremsstrahlung emission signal during plasma disruptions scenario as measured with the ITER hard x-ray monitor has been simulated for the first time aiming on optimizing the design parameters of this diagnostic. The possible dynamic range for the detection of confined REs is studied as well. The effect of the shape of the runaway distribution function in the momentum space on the observed diagnostic signal is also studied and briefly discussed.